Occurrence of Severe Haematometra with CEH-Pyometra, Endometrial Polyps and Cystic Ovarian Disease in a Dog - Gulia, Nakul; Bisla, Amarjeet; Deshmukh, Sidhartha; Singh, Ashwani Kumar; Honparkhe, Mrigank (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Hematometra (collection of blood contents in the uterus) or metrorrhagia (uterine bleeding) is an uncommon life threatening emergency clinical condition affecting dogs (Troxel et al., 2002). There are various etiologies documented for hematometra in dogs which are postpartum subinvolution of placental sites (Dickie and Arbeiter, 1993), anticoagulant rodenticide (warfarin) toxicity (Padgett et al., 1998), coagulation deficiency, uterine trauma, neoplasia, placental necrosis, idiopatheic prepubertal metrorrhagia, uterine serosal inclusion cysts and postpartum endometritis (Feldman and Nelson, 1996). In hematometra, physical examination findings and clinical signs are inconclusive, but the dog can suffer from anemia with frank vulvar hemorrhage of an open-cervix type.